In-situ synthesis of needle-like PdO-decorated NiO thin films on Al2O3 substrates for high-performance H2 sensors. Issue 21 (1st November 2022) - Song, Zhidan; Zhang, Long; Zhou, Quan; Zhang, Ziang; Dong, Zhaobo; Nie, Lifan; Liu, Qingyi; Pan, Gebo
Abstract: Safety is an essential consideration in the utilization of hydrogen energy due to its potential risk of explosion. Thereby, the synthesis of hydrogen sensors with highly sensitive properties is required for the early detection of hydrogen leaks. Here, a low-cost process was applied to fabricate PdO-decorated NiO H2 sensors capable of detecting sub-ppm H2 concentration. Unlike the previous two-step noble metal modification strategy, in situ ultrasonic spray pyrolysis was used in this work to directly obtain the needle-like PdO decorated NiO structure. The doped PdO tends to segregate at grain boundaries of NiO in needlelike form and can inhibit crystal growth. The gas-sensing performance was investigated by the means of dynamic gas distribution. The results show that the gas response towards H2 could be enhanced significantly by PdO doping. Especially, the sprayed 2 at% PdO-decorated NiO film sensor shows the highest response and the lowest detection limit at 250 °C, with a response value of 82% to 50 ppm H2 and a detection limit of 500 ppb. It can be speculated that the surface state of NiO film could be heavily affected by PdO doping, which leads to the high performance of PdO-decorated NiO sensors.